Nipa-based bioethanol as a renewable pure engine fuel: A preliminary performance testing and carbon footprint quantification - Mateo, Nathaniel Ericson Ramos; Calderon, Aldrin; Agrupis, Shirley; Manzano, Loreli Faye Tejada; Baga, Christopher Camento; Fagaragan, Alennie (Center of Biomass & Renewable Energy (CBIORE), 2025)
The need for alternative fuels remains a growing concern in alleviating the depletion of fossil fuels for transportation to address one of the objectives of the Sustainable Development Goals (SDG 7: Alternative and Clean Energy) despite the emerging use of Electric Vehicles. Nipa fruticans has been introduced as a promising feedstock for bioethanol production, but its performance as a pure engine engine fuel must be determined, and its carbon footprint must be quantified to assess its impact on the environment were this paper aimed. The CO2 emissions of this study was quantified using ISO 14040 methodologies, considering direct and indirect emissions from production to utilization with key ethanol properties tested according to ASTM standards. A carbureted motorcycle was modified to a fuel injection (FI) system to assess fuel performance, with metrics like power output, consumptions, and emissions were evaluated. Results show that nipa-based bioethanol, H95F and H99F, can serve as renewable pure engine fuels, with carbon footprints of 0.2353 and 2.633 kg CO2eq per Liter respectively with 1.08% lower of kg CO2eq per Liter emissions and 32.7% lower production cost compared to fermented sugar. As pure engine fuel resulted in lowering CO emissions by 171.79% and 167.59%; and lower HC emissions 172.89% and 191.34% respectively compared to E10. These findings demonstrated the potential of nipa bioethanol as a clean and sustainable energy solution. It is recommended however that ethanol yield and distillation process be further improved and explore pure ethanol as alternative fuel to hybrid vehicles as 100% renewable vehicles.